Catalyzing Bond‐Dissociation in Graphene via Alkali‐Iodide Molecules. Issue 42 (16th September 2021) - Vats, Nilesh; Negi, Devendra S.; Singh, Deobrat; Sigle, Wilfried; Abb, Sabine; Sen, Suman; Szilagyi, Sven; Ochner, Hannah; Ahuja, Rajeev; Kern, Klaus; Rauschenbach, Stephan; van Aken, Peter A.
Abstract: Atomic design of a 2D‐material such as graphene can be substantially influenced by etching, deliberately induced in a transmission electron microscope. It is achieved primarily by overcoming the threshold energy for defect formation by controlling the kinetic energy and current density of the fast electrons. Recent studies have demonstrated that the presence of certain species of atoms can catalyze atomic bond dissociation processes under the electron beam by reducing their threshold energy. Most of the reported catalytic atom species are single atoms, which have strong interaction with single‐layer graphene (SLG). Yet, no such behavior has been reported for molecular species. This work shows by experimentally comparing the interaction of alkali and halide species separately and conjointly with SLG, that in the presence of electron irradiation, etching of SLG is drastically enhanced by the simultaneous presence of alkali and iodine atoms. Density functional theory and first principles molecular dynamics calculations reveal that due to charge‐transfer phenomena the CC bonds weaken close to the alkali‐iodide species, which increases the carbon displacement cross‐section. This study ascribes pronounced etching activity observed in SLG to the catalytic behavior of the alkali‐iodide species in the presence of electron irradiation. Abstract : Alkali metal and iodine atoms when deposited individually on the single‐layer graphene (SLG), their adsorption does not cause etching when exposed to electron beam of 80 kV in TEM. However, when deposited together, their simultaneous presence weakens the CC bond of the underlying SLG, which leads to etching and hole formation under prolonged electron irradiation.